ANALISIS ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED UNTUK MENGUKUR KINERJA KEUNGAN PADA PT INTEGRA INDOCABINET TBK PERIODE 2017-2019 - Sitanggang, Novelina Asriani; Nango, Grace B; Pangerapan, Sonny (Universitas Sam Ratulangi, 2021)
Financial performance measurement functions as a consideration tool for kreditor and investor in giving loan or investment for the company. Until now the financial ratio analysis is still popular to measure the financial performance of a company. However, financial ratio analysis has a limitation which is it does not consider the company capital expense. Economic Value Added (EVA) is a tool to measure financial performance based on the economic value added with considering the interest of the investor by counting the capital expense. Market Value Added (MVA) is a tool to measure financial performance by measuring the company ability in increasing wealth for the stakeholders. This research used qualitative descriptive method. The result showed that PT Integra Indocabinet Tbk had shown bad financial performance in 2017-2019 period projected by EVA because the company could not produce an economic value added (EVA<0), meanwhile based on MVA the company had shown good financial performance by increasing wealth for the stakeholder (MVA>0).